ECONOMIC CONDITION OF POST TIN MINING (CASE STUDY ON BANGKA BELITUNG ISLAND AS ONE OF THE LARGEST TIN PRODUCERS IN THE WORLD) - Kusumah, Echo (PEOPLE: International Journal of Social Sciences, 2017)
This study aims to determine the effect of economic conditions of the Bangka Belitung island on the level of public purchasing power and the active role of local government policy when the natural resources of tin that can be produced by the public is very minimal. Along with the passage of time, the economic growth of Bangka Belitung has decreased even though there is still non-tin potential in the form of plantation and fishery. The research instrument in the form of questionnaires was used to 40 respondents. The data analysis used is the analysis of frequency descriptive and factor analysis to process the data that have been collected. The result of data analysis shows that the variable of public purchasing power and active role of dominant government have medium category (57,5% and 52,5%) whereas factor of public purchasing power and active role of society have value 67,593% in explaining economic condition of post tin mining.